Addition of grape marc improves the silage of aerial parts of cassava plant - de-Oliveira, Jean-Neuton; Nunes-Lista, Fabio; Neto, João-Virgínio-Emerenciano; Chaves-Gurgel, Antonio-Leandro; Difante, Gelson-dos-Santos; Vinhas-Ítavo, Luís-Carlos; Bezerra-Fernandes, Patrick; Marques-Costa, Carolina; da-Silva-Santos, Rodrigo; Gama-de-Oliveira, William (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Although it is possible to preserve the aerial part of cassava in the form of silage, as demonstrated in previous studies, its low dry matter content can result in undesirable fermentation and increased effluent losses during silage, leading to a reduction in the final quality of the silage. A possible way to get around this problem would consist in mixing this silage with dehydrated by-products from the agroindustry. Objective: To evaluate the addition of dehydrated grape marc (DGM) to a silage of aerial parts of cassava (Manihot esculenta, Crantz) on the chemical composition, degradability and in vitro gas production of silage. Methods: A completely randomized experimental design was used, with two treatments: (I) silage of the aerial part of cassava without additive; (II) silage of the aerial part of cassava added with 10% dehydrated grape marc (DGM) in the natural matter, as an additive. After 30 days of fermentation, silages were evaluated to estimate the contents of dry matter (DM), crude protein (CP), ether extract (EE), neutral detergent fiber (NDF), total digestible nutrients (TDN), as well as pH, in vitro degradability, and cumulative gas production by semi-automatic in vitro gas production. Results: Addition of DGM did not affect CP, EE, NDF, nor TDN levels in silage. The DGM, however, promoted an increase in DM content (32.61 vs 30.31%) and a reduction in pH (4.00 vs 4.75) of the silage. The silage that received DGM presented higher degradability coefficients of soluble and potentially degradable fractions, which led to higher values of potential and effective degradability. Similarly, DGM promoted a reduction in particle colonization time (6.74 vs 10.01 h) and increased cumulative gas production (62.03 vs 57.82 mL/g DM). Conclusion: Addition of 10% dehydrated grape marc in the silage of aerial parts of cassava can be useful to reduce pH and increase dry matter contents of the silage.